Welche Bedeutung haben nationale Wirtschaftsordnungen für die Zukunft der EU? Der Beitrag der sozialen Marktwirtschaft - Ronald Clapham (OrdnungsPolitisches Portal (OPO), 2007)
National economic and social policies of European Union member states are restricted by international and supranational treaties and by effects of globalisation. Furthermore, in the European integration process many economic policy areas have been transferred completely or partly to EU. Under such circumstances, what is the future role of national economic systems? What could Social Market Economy contribute to European integration? The paper's thesis reads that national economic systems will maintain the basic function fostering a competition of ideas for further developing an open, competitive and social orientated European order. Institutional competition (or competition among systems) is helping to discover and test suitable concepts and institutional innovations for Europe. Contributions of Social Market Economy to EU's future economic and social system mainly can be seen in four areas. 1. A continuing intellectual and political dispute concerning concepts of interventionism and centralising in the European common market. With it, EUcitizens preferences for decentralising or centralising policy responsibilities should be acknowledged strongly. Principles of Social Market Economy - freedom, solidarity, subsidiarity - should be defended as guidelines for further European integration. 2. Strengthening and defending competitive order in Europe, which is far more than competition law. German contributions are, firstly, supporting a market model understanding competition as a normativefunctional order, incorporating freedom and efficiency elements. Secondly, stick to Germany's proposal setting up an independent cartel office on European level. 3. Defending the independence of the European System of Central Banks as guarantor for monetary stability. Having politically weakened the Stability and Growth Pact (1997) the principle of ECB's independence is becoming even more important. Requests for changing ECB's status and rising political pressure on ECB's Board of Directors should be rejected in order to develop a culture of stability. 4. The European Social Model should be compatible with opportunities for national competence in social policies. Following the principle of subsidiarity, EU members should have extensive competences institutionalising and financing their own social security systems. Institutional competition can be seen as an approach, open for learning from bestpractise-cases, as e.g. Denmark's flexicurity concept for labour markets. Competition among systems, arising from the existing - though restricted - national economic orders of EU member states, has the non-replaceble function discovering and controlling efficient concepts and institutional arrangements for the future of the European Union.
Keywords: 330; Institutional competition; Social Market Economy; subsidiarity principle; independence of ECB